The effects of restaurant attributes on satisfaction and return patronage intentions: Evidence from solo diners' experiences in the United States - Sohyun Bae; Lisa Slevitch; Stacy Tomas (Cogent Business & Management, 2018)
Purpose-This study examines the interrelationship among restaurant attributes (including food, service, and physical environment), satisfaction and return patronage intentions with a focus on solo diners' experiences.Design/methodology/approach- A web-based survey was conducted to collect data from solo diners who resided in the United States.Findings- The findings showed that perceived quality of food, service, and physical environment were positively related to solo diners' satisfaction. Satisfaction mediated the relationships between three service quality components and return patronage intentions. Additionally, perceived food quality had a direct positive effect on return patronage intentions of solo diners.Research limitations/implications- The data were collected from a convenience sample of solo diners in the United States; thus, the generalizability of the results is limited. Effects of only three factors were examined in terms of impact on satisfaction and patronage intentions. Other factors may be included in the future studies.Practical implications- The results provide restaurant managers with understanding of how food and service quality as well as restaurant's environment can improve solo diner's satisfaction and return patronage intentions.Originality/value- In addition to the examination of the mediating effect of satisfaction on the relationships among three types of perceived quality and return patronage intentions, the study is centered on solo diners, an influential and growing group of customers that has not received much research attention.
Keywords: 650